2019
DOI: 10.1007/jhep05(2019)174
|View full text |Cite
|
Sign up to set email alerts
|

Production and backreaction of spin-2 particles of SU(2) gauge field during inflation

Abstract: Primordial SU(2) gauge fields with an isotropic background lead to the production of spin-2 particles during inflation. We provide a unified formalism to compute this effect in all of the inflation models with isotropic SU(2) gauge fields such as Gauge-flation and Chromo-Natural inflation with and without spectator axion fields or the mass of the gauge field from the Higgs mechanism. First, we calculate the number and energy densities of the spin-2 particles. We then obtain exact analytical formulae for their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 78 publications
(211 reference statements)
0
91
0
Order By: Relevance
“…Existing studies of P-violating bispectra and trispectra [62][63][64][65][66][67][68][69][70][71][72][73][74][75] require the presence of either tensor modes or broken rotational symmetry. These studies are thus aimed to probe the P or CP of the inflaton background or the gravitational interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies of P-violating bispectra and trispectra [62][63][64][65][66][67][68][69][70][71][72][73][74][75] require the presence of either tensor modes or broken rotational symmetry. These studies are thus aimed to probe the P or CP of the inflaton background or the gravitational interactions.…”
Section: Introductionmentioning
confidence: 99%
“…12 Note that Ref. [25] introduces a more refined criterion based on the effect of the induced current on the gauge field background EOM. This corresponds to re-summing all non-linear terms and hence (as we have verified explicitly numerically), the condition δA 2 NA 1/2 /(Rψ) = 1/10 corresponds to an O(1) backreaction from the induced current.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the backreaction of the scalar particles on the SU (2) background is negligible in the viable parameter regions of the simplest axion-SU (2) models. In [33], the backreaction of the extra spin-2 field in this setup was analytically studied for all the inflationary models involving the SU (2) gauge field.…”
Section: Contentsmentioning
confidence: 99%
“…We also add an interaction between axion and the axial fermionic current, J µ5 ∂ µ ϕ/Λ, which is naturally expected in this type of models. We then calculate the backreaction of the fermions on the SU (2) and axion background dynamics during inflation, following the framework we have established in [31,33].…”
Section: Contentsmentioning
confidence: 99%
See 1 more Smart Citation